Ceratose pilar e ulerythema ophryogenes em mulher com monossomia do braço curto do cromosomo 18 Keratosis pilaris and ulerythema ophryogenes in a woman with monosomy of the short arm of chromosome 18 - Charles André Carvalho; André Vicente Esteves de Carvalho; Andrea Kiss; Giorgio Paskulin; Fernanda Mendes Götze (Sociedade Brasileira de Dermatologia, 2011)
A monossomia parcial do braço curto do cromosomo 18 (síndrome do 18p) caracteriza-se, principalmente, por atraso na aquisição da fala, retardo mental leve a moderado e baixa estatura. Relatamos o caso de uma paciente com esta síndrome associada à ceratose pilar extensa e ulerythema ophryogenes. Este é o quarto relato de caso que descreve tal associação, que desperta considerável interesse porque pode revelar uma região candidata a sede de genes responsáveis pela queratinização folicular Partial monosomy of the short arm of chromosome 18 (18p- syndrome) is characterized mainly by speech delay, mild to moderate mental retardation and short stature. We describe a patient with the 18psyndrome and widespread severe keratosis pilaris and ulerythema ophryogenes. This is the fourth case in which such an association has been reported. This association is of considerable interest because it may uncover a candidate genomic region and help to identify the gene responsible for follicular keratinization